Synthesis and characterization of the oxygen-deficient perovskite BaFe0.9-xY0.1CoxO3-δ (0 ≤ x ≤ 0.15) - Urusova, A; Bryuzgina, A; Cherepanov, V; Battle, P; Chin, C (Elsevier, 2016)
BaFe0.9-xY0.1CoxO3-δ (0 ≤ x ≤ 0.15) is shown to adopt the cubic perovskite structure at temperatures up to 1400 K in air. The oxygen vacancy concentration increases with both cobalt content and temperature, with BaFe0.75Y0.1Co0.15O2.35 being the most oxygen-deficient composition observed. At 700 K the conductivity is ∼2 S cm−1 across the whole composition range. Measurements of the Seebeck coefficient show that holes are the dominant carrier. The coefficient of thermal expansion is essentially constant above 800 K, but not at lower temperatures. Chemical reactivity tests, along with the coefficient of expansion, show that these perovskites would not be suitable electrodes for fuel cells with fluorite electrolytes but they might serve as permeable membranes in catalytic reactors.